Decyzje o środowiskowych uwarunkowaniach: akty związane czy uznaniowe, deklaratoryjne czy konstytutywne? Analiza prawna - Kosieradzka-Federczyk, Agata (Kwartalnik Prawa Publicznego, 2013)
The issue of the article is to put the decision on environmental conditions within the classification elaborated in doctrine concerning the characteristic of administrative decisions. First is – the constrained or discretionary act. The second regards the constitutive or declaratory characteristic. In the analysis is taken into account that the same name: decision on environmental conditions is given to the decision issued after screening procedure and the same when environmental impact assessment was carried out. As far as the first characteristic is concerned, this is less important, as in both case such decision is constrained. In second case decision on environmental conditions issued after screening proceeding should be qualified as declaratory act while decision issued after environmental impact assessment has more constitutive feathers.